2021
DOI: 10.1111/eva.13234
|View full text |Cite
|
Sign up to set email alerts
|

Association of putatively adaptive genetic variation with climatic variables differs between a parasite and its host

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 125 publications
1
6
0
Order By: Relevance
“…Here, we found that species within the same habitat had different patterns of genetic similarity to hypothetical restoration sites. This reflects earlier work examining climatic drivers of adaptation within these species (Walters et al 2020 a ; Walters et al 2021 a ) and suggests that different provenance approaches could be needed for species within the same habitats. Contrasting patterns of provenances and/or seed transfer zones have been previously observed in co‐occurring plant species (e.g.…”
Section: Discussionsupporting
confidence: 78%
“…Here, we found that species within the same habitat had different patterns of genetic similarity to hypothetical restoration sites. This reflects earlier work examining climatic drivers of adaptation within these species (Walters et al 2020 a ; Walters et al 2021 a ) and suggests that different provenance approaches could be needed for species within the same habitats. Contrasting patterns of provenances and/or seed transfer zones have been previously observed in co‐occurring plant species (e.g.…”
Section: Discussionsupporting
confidence: 78%
“…In some ways, increased dimensionality is ubiquitous with increased habitat heterogeneity, and habitat heterogeneity has been shown to drive signatures of adaptation to temperature and precipitation in tree species (Shryock et al, 2020 ; von Takach et al, 2021 ; Walters et al, 2021 ). While these studies did not explore dimensionality explicitly, their results nevertheless show that tree species are able to independently adapt to multiple types of environments.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is not surprising in light of the historical focus on angiosperm‐insect co‐diversification (Ehrlich & Raven, 1964 ; Farrell et al., 1992 ; Farrell, 1998 ; Futuyma & Peterson, 1985 ; Peterson & Denno, 1998 ). However, many of the same reasons to expect that insect herbivores and mutualists should evolve in response to their host plants apply to symbiotic fungi (e.g., Escudero 2015 ), bacteria (Harrison et al., 2017 ), and even parasitic or commensal plants (Jerome & Ford, 2002 ; Schneider et al., 2016 ; Walters et al., 2021 )—other cases in which a single associate individual lives most of its life on one host, and in which associates' geographic dispersal is limited by hosts' distribution. Moreover, plants are far from alone in hosting parasitic and mutualistic associates in intimate interactions.…”
Section: Discussionmentioning
confidence: 99%